2006
DOI: 10.1002/macp.200600390
|View full text |Cite
|
Sign up to set email alerts
|

Furanic‐Aromatic Copolyesters by Interchange Reactions between Poly(ethylene terephthalate) and Poly[ethylene 5,5′‐isopropylidene‐bis(2‐furoate)]

Abstract: An efficient and environmentally benign synthesis of 3‐organoselenylchromenones was accomplished via iron(III) chloride/diorganyl diselenides‐promoted intramolecular 6‐endo‐dig cyclization of alkynyl aryl ketone derivatives. The cyclization reactions proceeded cleanly under mild reaction conditions, and the desired chromenone derivatives were smoothly isolated in good yields. The methodology proved to be highly regioselective, giving only the six‐membered regioisomers and was carried out using iron(III) chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This is also reflected by the low values of $\overline L _{\rm n} ({\rm T})$ and $\overline L _{\rm n} ({\rm F})$ . These copolyesters exhibited the same microstructure as their homologs obtained by interchange reaction between the corresponding PET and PEF homopolyesters 26…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…This is also reflected by the low values of $\overline L _{\rm n} ({\rm T})$ and $\overline L _{\rm n} ({\rm F})$ . These copolyesters exhibited the same microstructure as their homologs obtained by interchange reaction between the corresponding PET and PEF homopolyesters 26…”
Section: Resultsmentioning
confidence: 76%
“…The synthesis of PET copolyesters can be carried out by melt polycondensation between monomers,18, 19 by ester interchange between homopolyesters,20–23 or by reaction of PET with lactones or cyclic oligoesters 24, 25. In a previous work, we described the synthesis of furanic‐terephthalic copolyesters by the high temperature ester interchange reaction between high molar mass PET and poly[ethylene 5,5′‐isopropylidene‐bis(2‐furoate)] (PEF) 26. A kinetic study showed that the block copolyesters formed at the beginning of reaction slowly rearranged to random copolyesters after 2 h reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Also more recently FCA dimers have been used in the synthesis of various copolymers, for example, in block copoly­(esters) with PET, random copolymers with TPA by melt condensation, , copolymers with sulfonated isophthalic acids, , and copolymers with hexamethylene diamine and ethylene glycol …”
Section: Polymers Based On Biomass-derived Monomersmentioning
confidence: 99%
“…55 Finally, such dimers have more recently been employed in the synthesis of copolymers such as block copoly(esters) with PET. 56 ii.…”
Section: Figure 8 Synthesis Of Polyesters From Furfural-dimer-based Diestersmentioning
confidence: 99%